’Tryeat’ Variety Halal Food E-Commerce System: A Review - Saralina, M.S.; Nurdiana, A. (Usim Press, 2024)
Minggu Penyelidikan Dan Inovasi Sains Dan Teknologi 2022 (MPIST 2022): “Synergizing Innovation And Research Through Science And Technology”/ Editor : Hanis Nadia Yahya, Norhidayah Azman, Shahrina Ismail, Farah Hamizah Puad, Umul Ain’syah Sha’ari, Mohd Fauzi Haris 7th December 2022 I Organized by: Fakulti Sains dan Teknologi